Expert evaluator for Horizon 2020 - Kanetis, Loukas (My University, 2026)
First stage evaluation; Horizon 2020 - Work Programme 2018-2020: Food security, sustainable agriculture and forestry, marine, maritime and inland water research, and the bio-economy; Action: Research Executive Agency; Call: H2020-SFS-2018-2020 (Sustainable Food Security)